THE SKID RESISTANCE OF ROAD SURFACINGS IN BANDUNG - Thambah Sembiring Gurukinan, J.
This thesis describes an investigation of the skid resistance characteristics of road surfaces in the Bandung area. Some measurements were also made at Ciawi-Cianjur Roads. Surface deterioration and pavement/shoulder geometry were also studied with regard to their possible influence on skid resistance in wet conditions. Measurements of skid resistance were made at 25 sites (53 sub-sites) using the British Portable Pendulum Tester. Texture depth was measured using the Sand Patch Method. Skid resistance was indicated in terms of British Pendulum Number (BPN) and Skid Number (SN), the latter parameter taking into account both surface microtexture and macrotexture Over 80 percent of Category A (difficult) sites failed to meet minimum recommedation of either BPN or SN. Some 25 percent of Category B sites had BPN values below the minimum value recommended. Skid Number does not take into account lower BPN values recommended for sites in this category, hence 75 percent of Category B sites fell below the minimum SN value recommended. A limited study of the influence of road surface conditions was made on representative sites; the results suggest that, for these particular sites, the observed level of deterioration would not have a significant effect on skid resistance in wet conditions. This aspect requires more detailed analysis. In general, transverse profile of the pavement was adequate, although substantial improvement is required in some cases. However, the accessibility of surface runoff to a drainage channel was generally very limited and in a number of cases the shoulder was higher than the edge of the pavement. Insufficient data was available to permit ranking of the different surface types investigated. Although reasons are advanced in the thesis for the incidence of a high or low value of skid resistance parameters at particular locations, no attempt has been made to analyse ih detail the reasons for the values.recorded overall as this would require information on traffic intensity, age of surfacing,mix design and quality control of constructions.